Genetically predicted ankylosing spondylitis is causally associated with psoriasis - Tian, Di; Zhou, Yuan; Chen, Yuting; Wu, Ye; Wang, Heng; Jie, Chunchun; Yang, Yan; Liu, Yaoyao; Wang, Haoyu; Zhou, Dian (Frontiers in Immunology, 2023)
Background: Previous observational studies have reported the striking association between ankylosing spondylitis (AS) and psoriasis, but the causal relationship between the two diseases remains unclear.Methods: Two-sample Mendelian randomization (MR) analysis with methods of inverse-variance weighted, MR-Egger regression, weighted median, and weighted mode was conducted to evaluate the bidirectional causal associations between AS and psoriasis. Effective single-nucleotide polymorphisms (SNPs) from genome-wide association studies (GWAS) were selected as instrumental variables (IVs). Sensitivity analyses were also applied to verify whether heterogeneity and pleiotropy can bias the results.We found positive causal effects of genetically increased AS risk on psoriasis (IVW: OR = 1.009, 95%CI = 1.005-1.012, P = 8.07E-07). Comparable outcomes were acquired by MR-Egger regression, weighted median, and weighted mode approaches. Nevertheless, we did not find significant causal effects of psoriasis on AS (IVW: OR = 1.183, 95%CI = 0.137-10.199, P = 0.879). The sensitivity analyses showed that the horizontal pleiotropy was unlikely to skew the causality. The leaveone-out analysis demonstrated that no single SNP can drive the MR estimates. No evidence of heterogeneity was found between the selected IVs.Our findings provide evidence that AS has positive causal effects on the risk of psoriasis in the European population.